Callus culture-derived regeneration and molecular characterization of regenerated Stevia rebaudiana: implications for steviol glycoside production and genetic stability - Biswas, Pritom; Kumari, Ankita; Modi, Arpan; Priyam, Amiya; Haque, Rizwanul; Ola, Mohammad Shamsul; Kumar, Sanjeev; Kumar, Nitish (Frontiers in Plant Science, 2025)
The plant Stevia rebaudiana (Asteraceae) is gaining popularity as a zero-calorie natural sugar substitute. This paper investigates the regeneration of S. rebaudiana from callus, emphasizing steviol glycoside (SGs) production and the evaluation of genetic similarity. The highest rate of callus induction (89.20%) and maximum biomass were obtained from leaf explants using Murashige and Skoog (MS) medium, optimized with the addition of Naphthalene acetic acid (NAA) and 2,4-Dichlorophenoxyacetic acid (2,4-D). MS medium containing NAA and 6-Benzylaminopurine (BAP) was most effective for shoot regeneration, yielding the highest shoot induction rate (87.77%) and robust plant growth. Rooting efficiency was significantly enhanced by using a quarter-strength MS medium with Indole-3-acetic acid (IAA), which produced the highest rooting percentage (88.40%) and longest roots (3.41 cm). The acclimatized plantlets demonstrated a survival rate of 77-78% and closely resembled the parent plants in morphology. It was indicated by HPLC analysis that SGs concentrations were significantly higher in the leaves of in vitro regenerated plants compared to callus, while ex vitro leaves showed the highest content of both the SGs. The consistent amplification profiles observed in the genetic analysis, conducted using not only Random Amplified Polymorphic DNA (RAPD) but also Inter Simple Sequence Repeats (ISSR) markers, revealed no polymorphic bands, suggesting minimal somaclonal variation. This study highlights the effectiveness of callus culture for enhancing steviol glycoside production and maintaining genetic stability in S. rebaudiana.